(untitled) (CIPEEX, 2025)
COVID-19, caused by the SARS-CoV-2 virus, was discovered in 2020, with the pandemic originating in Hubei, China, in December 2019, and spreading rapidly worldwide. Patients presented symptoms of acute respiratory infection, with some progressing to severe complications such as acute respiratory distress syndrome (ARDS) and respiratory failure. Fear and the rapid spread of the disease led to an increase in self-medication with drugs such as ivermectin, azithromycin, chloroquine, and nitazoxanide, whose efficacy against COVID-19 was unproven. This study aimed to analyze the profile of adverse event notifications associated with nitazoxanide and ivermectin before and during the pandemic, using data from the VigiMed platform. The comparative analysis of the periods revealed a significant increase in adverse event notifications during the pandemic, highlighting the expanded and unfounded use of these medications. Furthermore, notifications increased in number and severity, with an emphasis on self-medication and changes in the profile of notifiers. In conclusion, the findings underscore the need for clear, evidence-based communication by health authorities and continuous surveillance of the off-label use of medications, especially during public health crises, to prevent an increase in adverse events and the overload of health systems.